The Effects of Social Media on Literacy Development among Pupils in Junior High Schools in Ghana - Ghanney, Robert Andrews; Antwi, Theresa; Agyeman, Edmond Amoako (Advances in Social Sciences Research Journal, 2017)
The study sought to investigate the effects of social media on literacy development among pupils in junior high schools particularly on their perception about the nature of literacy, identifying major social media network sites and their mass usage among pupils as well as the effects of social media and social networking sites on pupils’ language learning and literacy development within the context of socio-cultural and social learning theories. To achieve the objectives of this study, a case study design was used which comprised the use of interviews to solicit pupils’ responses on the effects of social media on literacy development. The population of the study consisted of all JHS pupils in the Asante-Akim South District in the Ashanti region of Ghana. A purposive sampling technique was used to select 25 pupils (14 females, 11 males) from three junior high schools. The data were analyzed using thematic analysis (qualitative content and document analyses), table with description and data triangulation. The findings showed participants’ exposure to major social media tools and social networking sites such as Facebook, Short Message Services (SMS), WhatsApp, Twitter and You Tube likewise online practices such as chatting, blogging, watching movies, listening to audios, image sharing, and so on. The study in addition revealed that social media tools and online practices influence participants’ reading skills and habits, writing skills and speaking in every way. This research recommends the strict application of Ghana Education Service rules and parental guidance on electronic devices usage in schools, homes and the promotion of social media networks for educational purposes.